Investigação acerca do conceito de vida segundo a relação entre normalidade e patologia na obra de Georges Canguilhem - Santos, Danilo Dos [UNIFESP] (2019)
The present research aims to investigate the concept of life constructed throughout the work of Georges Canguilhem from its underlying concepts, namely: normal and pathological, science and technique, norm, value, fact and death. In other words, we aim to discuss life from what it produces and at the same time constitutes it. That’s because, throughout his philosophical project, Canguilhem, through what has become known as "historical epistemology," elaborates a new way of making history and philosophy of science and of understanding the development of scientific knowledge in the light of philosophical analysis, therefore, launches a new perspective on problems related to some concepts, among them, the concept of life. The French philosopher and physician will understand life in the light of the concepts of normality and pathology, health and illness, as a dynamic polarity, as the form and power of the living, and in this way will attribute to its structure the dynamic relation of contraries, negative values and, unlike some artificial stability that historically a certain positivist and mechanistic interpretation attempted to construct in order to make life an object of science. In this way, we will make an exegesis into Canguilhem’s philosophical project about life, articulating the concepts quoted in different moments of Canguilhem thought, which will culminate in a new conception of the concept of life that, in short, will reaffirm the originality of the living being, mostly the living human, as opposed to the readings that seek to conceive the organism as a machine.